Fundamentals of electromagnetic levitation : engineering sustainability through efficiency - Sangster, Alan J. (Institution of Engineering and Technology, 2012)
"This book aims to make aspiring and existing electrical engineers aware of the efficiency implications of frictionless machines and how important this may be in a post fossil-fuel world in which the energy available from renewable sources is strictly limited."--EBL.
Keywords: Magnetic suspension.; elektronické knihy; electronic books